2021
DOI: 10.1093/genetics/iyab217
|View full text |Cite
|
Sign up to set email alerts
|

An extracellular matrix damage sensor signals through membrane-associated kinase DRL-1 to mediate cytoprotective responses inCaenorhabditis elegans

Abstract: We and others previously identified circumferential bands of collagen named annular furrows as key components of a damage sensor in the cuticle of Caenorhabditis elegans that regulates cytoprotective genes. Mutation or loss of non-collagen secreted proteins OSM-7, OSM-8, and OSM-11 activate the same cytoprotective responses without obvious changes to the cuticle indicating that other extracellular proteins are involved. Here, we used RNAi screening to identify protein kinase DRL-1 as a key modulator of cytopro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 88 publications
5
13
0
Order By: Relevance
“…Although these proteins are expressed at low levels, we detected the mGL::FLR-4 and mKate2::DRL-1 proteins at the intestinal plasma membrane (Fig. 3D), consistent with over-expression studies of FLR-4 and DRL-1 (Kobayashi et al 2011; Wimberly and Choe 2022). Furthermore, reciprocal co-immunoprecipitation studies demonstrated that HA::FLR-4 and FLAG::DRL-1 interact (Fig.…”
Section: Resultssupporting
confidence: 83%
“…Although these proteins are expressed at low levels, we detected the mGL::FLR-4 and mKate2::DRL-1 proteins at the intestinal plasma membrane (Fig. 3D), consistent with over-expression studies of FLR-4 and DRL-1 (Kobayashi et al 2011; Wimberly and Choe 2022). Furthermore, reciprocal co-immunoprecipitation studies demonstrated that HA::FLR-4 and FLAG::DRL-1 interact (Fig.…”
Section: Resultssupporting
confidence: 83%
“…Loss or mutation of any one of 6collagen encoding genes ( dpy-2 , 3 , 7 , 8 , 9 , and 10) disrupts furrows and activates stress responses ( Dodd et al 2018 ); DPY-7 and DPY-10 antibodies and DPY-7::GFP fusion protein localize to furrows ( McMahon et al 2003 ; Miao et al 2020 ). These results and subsequent genetic studies are consistent with a furrow-associated damage sensor that regulates 3 conserved environmental stress responses via distinct, but overlapping, downstream signaling ( Dodd et al 2018 ; Wimberly and Choe 2022 ).…”
Section: Introductionsupporting
confidence: 73%
“…Caenorhabditis elegans develops through 5 stages delineated by synthesis and molting of cuticles ( Cox and Hirsh 1985 ; Johnstone 2000 ). Roles of furrow collagens in stress response regulation have only been studied in the terminal adult stage ( Dodd et al 2018 ; Wimberly and Choe 2022 ). The cuticle functions as a flexible collagenous barrier and exoskeleton in all stages, but there are differences that could influence environmental stress sensing.…”
Section: Introductionmentioning
confidence: 99%
“…Given difficulties interpreting basal mRNA differences and lack of correlation between stress response induction levels and male-biased stress resistance, we next used fluorescent transcriptional reporters for canonical osmotic, heat shock, and detoxification stress response genes ( gpdh-1p :: dsRed2 , hsp-16 . 2p :: GFP , and gst-4p :: GFP , respectively) [ 46 , 71 , 72 ] to determine if there were any major differences in distributions that may correlate with stress resistance. As shown in S3A and S4 Figs, fluorescence for these reporters was not clearly visible above background in either sex under basal conditions.…”
Section: Results and Conclusionmentioning
confidence: 99%